Exploring School Principals’ Experiences During the First Four Months of the Pandemic as a Way to Reimagine Inclusive Education - Anderson, Daniel John; MacCormack, Jeffrey; Sider, Steve (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
This study involved interviewing Canadian principals (N = 37) to determine how they responded to students with special education needs during the COVID-19 pandemic. Yamamoto et al.’s (2014) concept of critical incidents and Heine et al.’s (2006) meaning maintenance model were used to evaluate the transformational power of principals’ pandemic experiences in order to reimagine inclusive education. Findings revealed that these critical incidents broadly fell into four categories: 1) family support and the complications associated with partnering with parents virtually, 2) meeting students’ needs in new and often innovative ways, 3) disparities in student experiences as a result of virtual schooling and 4) responses required in light of logistical and technical challenges.